IoT Security and Privacy Issues: A Taxonomy - Mohamad Ibrahim Ladan (International Journal of Computers and Informatics, 2025)
The Internet of Things, IoT, is affecting almost every part of our life and it is connecting us in unprecedented ways. Every device we carry, own, or have at home or in office could be connected to the internet. It could be our air-conditioning, alarm system, smoke detector, doorbell, refrigerator, TV, water/energy meters, parking meters, pollution detectors, car navigation systems, and public or private transportation vehicles. This will lead us to be more in touch with our surroundings and eventually turn our communities and cities into fully integrated, smart, sustainable intelligent entities. All IoT-based transformations are now occurring to increase productivity and create a coordinated world across business and technologies, and to make our lives smarter and easier, however, this, as with any new technology, often comes with a cost in terms of new security and privacy challenges and risks. We, as users of this new technology are often too preoccupied by its wonderful benefits that we don’t even think about any possible privacy risks or security issues that this new technology might introduce. Moreover, the exchange, storage, processing and transfer of tremendous amounts of sensitive information has also given rise to severe security and privacy concerns that compromise the efficiency and usability of IoT. It has become a challenge for users to depend on such a vulnerable technology, where the IoT security risks outweigh its benefits. Hence, security and privacy requirement is one of the key challenges to the IoT’s growth and success, and different IoT applications and devices may require different levels of security. In this paper we review and classify the different security and privacy issues pertaining to IoT and their different uses and applications, and we discuss the different measures that can be put in place to alleviate and address these issues.
Keywords: Internet of Things; Internet of Things Security Issues; Internet of Things Privacy Issues